2015
DOI: 10.1002/2014ja020081
|View full text |Cite
|
Sign up to set email alerts
|

East‐west type precursor activity prior to the auroral onset: Ground‐based and THEMIS observations

Abstract: Using ground-based optical observations, we study an auroral breakup event, focusing on the wave-like signatures of the east-west (E-W) type auroral activities which appear before breakup. By conjunction with the Time History of Events and Macroscale Interactions during Substorms (THEMIS) P2 and P5 measurements, it is shown that the underlying wave mode can be identified as the ballooning mode. Considering the similarity of the wave-like characteristics derived from ground-based auroral and THEMIS spacecraft o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The constellation of the five satellites of Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission provides a unique possibility to investigate the spatial and temporal structure of the ULF waves observed in situ. For example, high-m Pc5 pulsations are often studied with THEMIS Du et al, 2011;Golovchanskaya et al, 2015;Le et al, 2017;Liu et al, 2011Liu et al, , 2013Melikyan et al, 2013;Sarris et al, 2009;Sibeck et al, 2012;Takahashi et al, 2013). However, those studies did not reach an unambiguous conclusion on the nature of the compressional Pc5 waves: Some authors concluded that they represent drift mirror modes, other authors insist on their Alfvénic nature, and several authors suppose that they can represent the slow magnetosonic modes.…”
Section: Introductionmentioning
confidence: 99%
“…The constellation of the five satellites of Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission provides a unique possibility to investigate the spatial and temporal structure of the ULF waves observed in situ. For example, high-m Pc5 pulsations are often studied with THEMIS Du et al, 2011;Golovchanskaya et al, 2015;Le et al, 2017;Liu et al, 2011Liu et al, , 2013Melikyan et al, 2013;Sarris et al, 2009;Sibeck et al, 2012;Takahashi et al, 2013). However, those studies did not reach an unambiguous conclusion on the nature of the compressional Pc5 waves: Some authors concluded that they represent drift mirror modes, other authors insist on their Alfvénic nature, and several authors suppose that they can represent the slow magnetosonic modes.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention was paid to the nearly northsouth aligned auroral structures originating at the poleward auroral boundary and progressing to lower latitudes, which were considered as substorm precursors (e.g., Rostoker et al, 1987). Golovchanskaya et al (2015) focused on the wavelike signatures of the east-west type of auroral activities, which appear before the breakup and may be related to ballooning waves propagating in the plasma sheet. In fact, any form of optical presubstorm activity could be considered as a precursor of the onset, so such investigations need to continue to clarify the situation.…”
Section: Preonset Phenomenamentioning
confidence: 99%
“…vection velocity. A detail description of the system was given by Greenwald et al (1995) and Chisham et al (2007).…”
Section: Instrumentationmentioning
confidence: 99%